Development of Android Game-Based Media to Enhance Students' Arabic Grammar Skills - Widodo Febri Utomo; Asrowi Asrowi; Herry Widyastono (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
The integration of technology into education continues to evolve, with Android-based game media offering new opportunities for more engaging learning experiences. However, there is still a lack of research that specifically focuses on developing Android-based game media to improve Arabic grammar skills at the Madrasah Ibtidaiyah level. This study aims to develop Android-based game media to enhance students’ Arabic grammar skills in Madrasah Ibtidaiyah. Utilizing a Research and Development (R&D) approach with the Alessi & Trollip development model, the research involved media experts, subject matter experts, practitioners, and 40 students. Data were collected through observation and questionnaires, then analyzed using both qualitative and quantitative methods. During alpha testing, the media received an average feasibility score of 91.17% from experts and practitioners, categorized as "very strong." In the beta testing phase, 40 students participated, and the media achieved an average score of 88.00%, also rated as "very strong." These results indicate that the Android-based game media is highly feasible and effective for supporting Arabic grammar instruction. The study concludes that this media can serve as a valuable supplementary tool to improve grammar proficiency and increase student engagement in Arabic language learning at the elementary level.